2009
DOI: 10.1158/1535-7163.mct-09-0056
|View full text |Cite
|
Sign up to set email alerts
|

A novel hTERT promoter–driven E1A therapeutic for ovarian cancer

Abstract: Currently, an effective gene therapy strategy, which not only retains cancer-specific expression but also limits toxicity, has yet to be developed for ovarian cancer. Mounting reports over the years have shown that human telomerase activity is significantly elevated in cancer cells compared with normal cells. In this study, we evaluated the human telomerase reverse transcriptase (hTERT; T) promoter and showed that it can direct target gene expression preferentially in ovarian cancer cells. However, its promote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…The tumor-specific hTERT promoter has been successfully used in the gene therapy of ovarian cancer (21,22). Nevertheless, the activity of the hTERT promoter in ovarian tumor cells is often too low for effective targeted gene therapy (5). The TSTA system, including the transcriptional activator GAL4-VP16 and G5E4T regulatory element (a small promoter that is responsive to GAL4), has markedly enhanced the activity of the corresponding TSP (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor-specific hTERT promoter has been successfully used in the gene therapy of ovarian cancer (21,22). Nevertheless, the activity of the hTERT promoter in ovarian tumor cells is often too low for effective targeted gene therapy (5). The TSTA system, including the transcriptional activator GAL4-VP16 and G5E4T regulatory element (a small promoter that is responsive to GAL4), has markedly enhanced the activity of the corresponding TSP (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous promoters have been used in targeted gene therapy for ovarian cancer, including secretory leukocyte protease inhibitor, ovarian-specific promoter and human epithelial tissue-specific transcription factor promoter, these promoters are neither ovarian cancer-specific nor epithelium-specific, and may even be active in normal cells (3). By contrast, the human telomerase reverse transcriptase (hTERT) promoter is only activated in ovarian cancer cells with high telomerase activity, and therefore is highly suitable for the gene therapy of ovarian cancer (4,5). However, the activity of tumor-specific promoters is often too weak to mediate the desired gene therapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…The human telomerase reverse transcriptase (T) is highly expressed in a majority of cancer types but not in normal cells, which allows it to be used as a tumor biomarker (15,17,18). Previously, we identified and validated the specificity of the T promoter in ovarian cancer and showed that its activity was enhanced by the VISA amplification system (15).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids pGL3-T-Luc, pGL3-Survivin-Luc, pGL3-Clandin-4-Luc, pGL3-FASN-Luc, pGL3-b-cateinin-Luc, and pGL3-CMV-Luc containing the T, survivin, claudin-4, FASN, b-catenin, and CMV promoter, respectively, to drive the expression of the firefly luciferase gene were previously described (14,15,19,21,26). The VISA amplification system was incorporated into the pGL3-T-Luc plasmid to create pGL3-T-VISA-Luc.…”
Section: Preparation Of Plasmids and Liposomementioning
confidence: 99%
See 1 more Smart Citation